Ржёт ли солнце? (к вопросу о трудностях художественного перевода) - Viktoria Lebovics (Slavica TerGestina, 1997)
The author, in analyzing some mistakes and errors in the Hungarian translation of a part of Tshingiz Aitmatov's novel, has made an effort to find possible explanations and reasons for them. Phonetical similarity of foreign words together with the context as a false friend of the translator enforced by uncertain knowledge of the translator is one such reason. Another explanation is that sometimes the translator is unaware of the fact that his translation is illogical, sometimes unnecessary repetitions and explanations at both a textual and a lexical level are added, and another mistake is connected with the inappropriate choice of a word from a range of synonyms.